Contextualiser les comportements politiques par le territoire. - Jessica Sainty (L'Espace Politique)
This article focus on dialogue opened between electoral sociology and geography, in the aim to understand more in-depth political behavior with a territorial look. This dialogue starts with the observation of progressive disappearance of the territorial look in electoral sociology studies from 1960’s, which reappear in the early 1990’s in the form of a contextual look. Then, the use of geography helps to detect and define territorial influence on political behavior. Finally, this dialogue between electoral sociology and geography seems to be useful in making more dynamic the understanding of political behavior of individuals.